AI-Powered Influence: Unveiling Consumer Engagement and Purchase Intentions in Malaysia - Krishnan, Vijayaletchumy; Guo, Jiayuan; Nusraningrum, Dewi; Widyanty, Winda; Pentang, Jupeth T. (Journal of Ecohumanism, 2024)
Artificial intelligence (AI) has revolutionized marketing strategies, particularly in the realm of influencer marketing, which plays a crucial role in shaping consumer behavior. This study examines the impact of AI-driven influencer marketing on customer engagement, purchase intentions, and consumer behavior in Malaysia, with consumer trust serving as a moderating variable. A quantitative research design was adopted, and data were collected from 500 respondents via an online survey. The results, analyzed using Smart PLS, reveal that AI-driven influencer marketing exerts a positive influence on customer engagement, purchase intentions, and consumer behavior. Moreover, consumer trust significantly moderates these relationships, intensifying the positive effects of AI-driven marketing efforts. These findings underscore the transformative potential of AI in optimizing influencer marketing strategies and emphasize the importance of cultivating consumer trust to enhance marketing effectiveness. This study contributes to the growing body of literature on AI in marketing and offers practical insights for businesses seeking to engage consumers more effectively. Theoretical and practical implications, along with limitations and directions for future research, are also discussed.